A rapid, ratiometric, enzyme-free, and sensitive single-step miRNA detection using three-way junction based FRET probes. (6th February 2018) - Luo, Qingying; Liu, Lin; Yang, Cai; Yuan, Jing; Feng, Hongtao; Chen, Yan; Zhao, Peng; Yu, Zhiqiang; Jin, Zongwen
Abstract: MicroRNAs (miRNAs) are single stranded endogenous molecules composed of only 18–24 nucleotides which are critical for gene expression regulating the translation of messenger RNAs. Conventional methods based on enzyme-assisted nucleic acid amplification techniques have many problems, such as easy contamination, high cost, susceptibility to false amplification, and tendency to have sequence mismatches. Here we report a rapid, ratiometric, enzyme-free, sensitive, and highly selective single-step miRNA detection using three-way junction assembled (or self-assembled) FRET probes. The developed strategy can be operated within the linear range from subnanomolar to hundred nanomolar concentrations of miRNAs. In comparison with the traditional approaches, our method showed high sensitivity for the miRNA detection and extreme selectivity for the efficient discrimination of single-base mismatches. The results reveal that the strategy paved a new avenue for the design of novel highly specific probes applicable in diagnostics and potentially in microscopic imaging of miRNAs in real biological environments.